Learning Style Of Efl Learners On Reading Comprehension At SMPN 2 Pematangsiantar - Labora Manik; Dumaris E. Silalahi; Basar Lolo Siahaan (CV Putra Publisher, 2023)
This research aims to determine the Learning Style of EFL Learners in Reading Comprehension at Smpn 2 Pematangsiantar. This research was conducted using qualitative methods. Qualitative methods are research that collect data in the form of words or images, not numbers. This research was carried out in September 2023 and was carried out at SMPN 2 Pematangsiantar which is located at Jl. Rajamin Purba, Sofa Hill, Siantar Sitalasari, Pematangsiantar City, North Sumatra. The primary data in this research are students. Secondary data in the form of research journals, relevant books. This data was obtained from interviews with research participants, namely class IX students of SMP Negeri 2 Pematangsiantar for the 2023/2024 academic year. Researchers conducted research in class IX-11. Data collection is an important step in research, because the main aim of research is to obtain data. The procedures applied to analyze data are data reduction and data display. Researchers found three dominant student learning styles, namely: visual learning style, auditory learning style, then kinesthetic learning style and one combination of learning styles, namely: kinesthetic-auditory/musical. There are three students who have a visual learning style. After that, there were three students who had an auditory learning style, then there were two students who had a kinesthetic learning style, and finally there was one student who had a kinesthetic-auditory (musical) learning style.